Ni3Sn4-composed die bonded interface rapidly formed by ultrasonic-assisted soldering of Sn/Ni solder paste for high-temperature power device packaging. (15th October 2016) - Ji, Hongjun; Li, Minggang; Ma, Shu; Li, Mingyu
Abstract: The time-consuming of transient-liquid-phase is a big challenge for the die bonding. In this paper, a novel rapid bonding method plus alloying design was proposed to cheaply fabricate SnNi intermetallic joint for high temperature electronic packaging. The ultrasonic effect and the evolution of the joint microstructures, shear strength as a function of Ni content were systemically investigated. The amount of Ni3 Sn4 in the joint increased with the addition of Ni, and when the Ni content reached 24 wt.%, the joint consisted of nearly sole Ni3 Sn4 with a high shear strength of 43.4 MPa was achieved. After aging at 300 °C for 72 h in air, the shear strength of the joint obtained with smaller Ni content solder showed great improvement because of the phase transformation of residual Sn to Ni3 Sn4, but for the Sn-24 wt.%Ni and Sn-30 wt.%Ni, it showed a little decrease due to the grains coarsening of Ni3 Sn4 . The acoustic cavitation and streaming effects dramatically accelerates the reaction of Ni and Sn during the ultrasonic-assisted soldering. The joint obtained by the Sn-24 wt.%Ni solder has the best potential to be applied in the power electronic packaging. Graphical abstract: Highlights: Sn/Ni hybrid solder by pressureless and rapid ultrasonic-assisted soldering was designed for die bonding. Nearly sole Ni3 Sn4 joint was achieved with Sn-24 wt.% Ni solder at 250°C within 10s. The microstructure, shear strength and fracture modes of the joint as function of Ni content were systemically investigated. High re-melting temperature join with shear strength of 43.4MPa after bonding and 33.4MPa after aging at 300°C was obtained.